Sensorimotor Difficulties Are Associated with the Severity of Autism Spectrum Conditions - Hannant, Penelope; Cassidy, Sarah; Tavassoli, Teresa; Mann, Francesca (Frontiers in Integrative Neuroscience, 2016)
Present diagnostic criteria for autism spectrum conditions (ASC) include social communication and interaction difficulties, repetitive behaviour and movement, and atypical sensory responsivity. Few studies have explored the influence of motor coordination and sensory responsivity on severity of ASC symptoms. In the current study, we explore whether sensory responsivity and motor coordination differences can account for the severity of autistic behaviours in children with ASC. 36 children took part: 18 (13 male, 5 female) with ASC (ages 7-16: mean age 9.93 years) and 18 (7 male, 11 female) typically developing (TD) children (ages 6-12; mean age 9.16 years). Both groups completed a battery of assessments that included motor coordination, sensory responsivity, receptive language, non-verbal reasoning and social communication measures Children with ASC also completed the Autism Diagnostic Observation Schedule and Autism Diagnostic Interview – Revised.. Results showed that children with ASC scored significantly lower on receptive language, coordination and sensory responsivity and a sensorimotor subscale, Modulation of Activity (MoA) compared to the TD group. In the ASC group, MoA significantly predicted ASC severity across all ASC measures; receptive language and sensory responsivity significantly predicted parental reported autism measures; and coordination significantly predicted examiner observed reported scores. Additionally, specific associations were found between the somatosensory perceptive modalities and ASC severity. The results show that sensorimotor skills are associated with severity of ASC symptoms; furthering the need to research sensorimotor integration in ASC and also implying that diagnosis of ASC should also include the assessment of both coordination deficit and atypical sensory responsivity.